Guidelines for Operation and Usage of County Kitchens in the State of Florida - Amarat Simonne; Tim Wilson; Geralyn Sachs; Joanne Cooper; Brenda Morris; Steven von Bodungen; Liz Felter (EDIS)
In recent years, many people have become interested in developing small food businesses. Using county kitchens to make food products for sale may seem very attractive. However, because of different local, state, and federal regulation requirements, there may be some confusion and unresolved conflicts among different parties as to the legalities and practicalities involved. This 3-page fact sheet provides guidelines and advice for Florida Extension personnel to use when determining the appropriate usage for their kitchen facilities, based on a situation in one Florida county. The publication covers utilization, roles and responsibilities, and potential liability issues relevant to the use of county kitchens, providing some potential solutions to conflicts for all parties. Written by Amarat Simonne, Tim Wilson, Geralyn Sachs, Joanne Cooper, Brenda Morris, Steven von Bodungen, and Liz Felter, and published by the UF Department of Family, Youth and Community Sciences, August 2016.